2001
DOI: 10.1089/108729101300003681
|View full text |Cite
|
Sign up to set email alerts
|

Concerns of Pregnant Women about Being Tested for HIV: A Study in a Predominately Mexican-American Population

Abstract: More than 90% of pediatric acquired immune deficiency syndrome (AIDS) cases are due to mother-to-child (vertical) transmission. Medical intervention can reduce the risk of vertical transmission human immunodeficiency virus (HIV) from 25% to less than 8%. However, studies have suggested that approximately one-fourth of women may refuse HIV testing as part of routine prenatal care. The purpose of this study was to identify concerns that pregnant women might have that would impact their decision to undergo HIV te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Young people with strong familism value may view testing as a negative reflection on the family unit due to the stigma associated with HIV and the fear of sexual activity and orientation disclosure (Perez and Cruess 2014). In a sample of pregnant Latinas, concerns for being perceived as sexually promiscuous were the primary reason for not testing (Parra et al 2001). In a study of human papillomavirus vaccination, Latino parents exhibited a higher trend toward the belief that their daughters were not at risk for sexually transmitted infections compared to non-Latino parents (Watts et al 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Young people with strong familism value may view testing as a negative reflection on the family unit due to the stigma associated with HIV and the fear of sexual activity and orientation disclosure (Perez and Cruess 2014). In a sample of pregnant Latinas, concerns for being perceived as sexually promiscuous were the primary reason for not testing (Parra et al 2001). In a study of human papillomavirus vaccination, Latino parents exhibited a higher trend toward the belief that their daughters were not at risk for sexually transmitted infections compared to non-Latino parents (Watts et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on acculturation, assessed as place of birth, reported that US-born participants were more likely to have been tested for HIV (Chen, Gallant, and Page 2012;Oster et al 2013;Uribe et al 2009). Lower levels of acculturation, based on language use and preference, has been associated with lower likelihood of testing (Parra et al 2001). Among Latino participants in a population-based interview study, choosing to interview in Spanish was predictive of delayed testing after adjusting for age, education, drug injection and country of origin (Wohl, Tejero, and Frye 2009).…”
mentioning
confidence: 99%
“…10 For this reason, it is recommended that each country should declare criteria for prenatal HIV testing according to the prevalence of AIDS in their country and then establish policies that should consider pregnant women's individual right of decision making, their willingness and their privacy and safety, and should also protect them from discrimination and stigmatization. 6,10,11 This study was designed to obtain verifiable data about attitudes and preferences of pregnant women and prenatal care providers towards prenatal HIV testing.…”
Section: Introductionmentioning
confidence: 99%
“…Prevention of mother to child transmission of HIV (PMTCT) can be through provision of anti retroviral drugs (ARVs) and safe infant feeding counselling and practices [15,16] Despite the low cost for these short course ARV regimens, implementation of PMTCTprograms faces many challenges including low uptake of Voluntary Counselling and Testing (VCT) [17][18], failure to return for HIV test results, failure to return for follow up visits before starting antiretroviral therapy or lack of adherence to drugs [19], fear of husbands and relatives, stigmatization by the general public, denial of sero-status, non-disclosure of serostatus, lack of consistent information, pro-breastfeeding cultural beliefs, low literacy levels, poverty, and lack of alternative feeds [20].…”
Section: Introduction and Literature Review mentioning
confidence: 99%